THE IMPACT OF THE PARTNERSHIP BETWEEN BANK SYARIAH MANDIRI GRESIK BRANCH AND BMT PERFORMANCE (CASE STUDY OF BMT MANDIRI SEJAHTERA IN GRESIK REGENCY) - Ghofur, Abdul (Universitas Airlangga, 2015)
This study aimed to obtain the impact of Bank Syariah Mandiri branch partnership Gresik on the performance of BMT Mandiri Sejahtera consists of Financial Performance them and social performance. The financial performance of which is Return on Assets (ROA),Return on Equity (ROE), Non Performing Financing (NP), Financing to Deposit Ratio (FDR) and social performance is Zakat, Infak, and shodaqoh (ZIS) and Qardul Hasan. These results indicate a positive impact on performance BMT Mandiri Sejahtera after partnering with Syariah Mandiri Bank of Branch Gresik. Keyword : partnership, performance, BMT Mandiri Sjahtera